Molecular Imaging of Autoimmune Diseases and Inflammation - S. Anna Sargsyan; Joshua M. Thurman (Molecular Imaging)
Molecular imaging methods allow the noninvasive detection and localization of specific molecules. Agents that report on molecular disease biomarkers can be used to diagnose and monitor disease. Many inflammatory diseases have molecular signatures within altered tissues. Although tissue biopsy is still the gold standard for detecting these signatures, several molecular imaging markers have been developed. Pharmacologic agents that block specific immune molecules have recently entered the clinic, and these drugs have already transformed the way we care for patients with immune-mediated diseases. The use of immunomodulatory drugs is usually guided by clinical assessment of the patient's response. Unfortunately, clinical assessment may miss the signs of inflammation, and many of the serologic markers of immune-mediated diseases correlate poorly with the underlying inflammatory activity within target tissues. Molecular imaging methods have the potential to improve our ability to detect and characterize tissue inflammation. We discuss some of the molecular signatures of immune activation and review molecular imaging methods that have been developed to detect active tissue inflammation.